2019
DOI: 10.1016/j.gene.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between the FTO gene variant and alcohol consumption and binge and problem drinking in different gene-environment background: The HAPIEE study

Abstract: BACKGROUND: Alcohol intake and tobacco smoking have significant negative health consequences and both are influenced by genetic predispositions. Some studies suggest that the FTO gene is associated with alcohol consumption. We investigated whether a tagging variant (rs17817449) within the FTO gene is associated with alcohol intake, problem drinking and smoking behaviour. METHODS: We analysed data from 26,792 Caucasian adults (47.2% of males; mean age 58.9 (±7.3) years), examined through the prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
10
0
3
Order By: Relevance
“…Moreover, in the crossphenotype association study, the notable identified SNP rs10492872 mapped to FTO is shared by two trait pairs of ground coffee/BMI and instant coffee/BMI, and its effects on ground coffee and instant coffee are in opposite directions, so as rs11660753 mapped to SMIM21 (Tables 1C, D). FTO gene is the first candidate gene of obesity, and it is also related to a variety of other phenotypes, such as alcohol intake (36), C-reactive protein levels (37), etc. A recent study has found that FTO can help cancer cells escape immune surveillance (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the crossphenotype association study, the notable identified SNP rs10492872 mapped to FTO is shared by two trait pairs of ground coffee/BMI and instant coffee/BMI, and its effects on ground coffee and instant coffee are in opposite directions, so as rs11660753 mapped to SMIM21 (Tables 1C, D). FTO gene is the first candidate gene of obesity, and it is also related to a variety of other phenotypes, such as alcohol intake (36), C-reactive protein levels (37), etc. A recent study has found that FTO can help cancer cells escape immune surveillance (38).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that the effect of FTO polymorphisms on alcohol consumption may be altered under different environmental conditions. 32 However, there were some limitations in our present study. First, different types of BC including the status of hormone receptors and also the stage of BC were not considered.…”
Section: Discussionmentioning
confidence: 79%
“…However, Hubacek et al found no association between this polymorphism and alcohol consumption. A recent study indicated that the effect of FTO polymorphisms on alcohol consumption may be altered under different environmental conditions 32 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the cross-phenotype association study, the notable identi ed SNP rs10492872 mapped to FTO is shared by two trait pairs of ground coffee/BMI and instant coffee/BMI, and its effects on ground coffee and instant coffee are in opposite directions, so as rs11660753 mapped to SMIM21 (Table 1). FTO gene is the rst candidate gene of obesity, and it is also related to a variety of other phenotypes, such as alcohol intake [40], C-reactive protein levels [41], etc. A recent study has found that FTO can help cancer cells escape immune surveillance [42].…”
Section: Discussionmentioning
confidence: 99%